(untitled) (Texas Journal of Engineering and Technology, 2022)
In this article, the teaching of science in physics and show them problem demonstrated experience related to improving the magnetic properties of the substance of the issue of creating a program information from today’s modern day interactive lessons and methods of use technology provides information about the advantages of the organization